Validitas Hukum Permendag Nomor 29 Tahun 2019 Tentang Ketentuan Ekspor dan Impor Hewan terhadap Eksistensi Undang-Undang Jaminan Produk Halal Indonesia - Nurul Miftah Jannah; Andi Syafrani (Faculty of Sharia and Law State Islamic University Syarif Hidayatullah Jakarta, 2020)
The issues that will be examined in this article are related to the legal validity of the Minister of Trade Regulation Number 29 of 2019 concerning the Export and Import of Animal and Animal Products to the existence of the Halal Product Guarantee Law. The problem is related to the legality of the inclusion of the Halal Product Guarantee Law in the consideration and legal basis of MOT Number 29 of 2019 and the legal validity of the Minister of Trade Regulation Number 29 of 2019 faced with the existence of the Halal Product Guarantee Law. This research method uses a normative juridical approach by analyzing the problems associated with statutory regulations (statute approach) in the field of consumer protection law. The results in this study indicate that the existence of the problem (conflict) is the philosophical impact that is incurred against the theory of legal protection and legal morality where a norm basically aims to protect consumers, especially Muslim consumers in their rights. Sociologically, this research also has an impact on decreasing moral stability and certainty in the law that applies to the inclusion of halal certification in imported animal products and animal products in Indonesia after the issuance of MOT 29/2019 concerning the provisions of Export and Import of animals and animal products, so that it can be issued. cause multiple interpretations and misunderstandings from various circles.